TUGAS DAN WEWENANG BADAN PENGAWAS PEMILIHAN UMUM DALAM MENGATASI SENGKETA PEMILU KEPALA DAERAH - KMS. Novyar Satriawan Fikri; Ali Azhar (Sekolah Tinggi Pariwisata Mataram, 2023)
This research aims to determine the extent of the implementation of the duties and authority of the Indragiri Hilir Regency General Election Supervisory Body in supervising the implementation of the General Election, especially to resolve the dispute over the Regional Head Election, Indragiri Hilir. Apart from that, this research also aims to find out what factors influence or hinder the implementation of supervision in the General Election held by the Regional General Election Commission of Indragiri Hilir Regency. This research uses empirical and normative research methods. The data obtained was processed and analyzed both qualitatively and quantitatively. The research results obtained show that the implementation of supervision by the Indragiri Hilir Regency General Election Supervisory Agency regarding the implementation of the General Election, especially to resolve regional head election disputes has been carried out in accordance with applicable laws and regulations. Apart from that, the Indragiri Hilir Regency General Election Supervisory Agency handles election cases and disputes, whether administrative in nature, ethical violations, or election criminal violations. The factors that influence the implementation of supervision by the Indragiri Hilir Regency General Election Supervisory Agency include limited personnel or supervisory apparatus, as well as limited infrastructure, for example the Indragiri Hilir Regency General Election Supervisory Agency office which has contract status